Telehealth Physical Therapy for Sports Medicine Rehabilitation: What Is Its Role in the Postpandemic Era?. Issue 10 (20th October 2022) - Kim, Billy I.; Peairs, Emily; Lander, Sarah; Antonelli, Christopher; Lau, Brian C.
Background: The adoption of telehealth visits for physical therapy (PT) has accelerated because of the COVID-19 pandemic. Patient reception of virtual PT at the outbreak of the pandemic was positive, but it is unclear how telehealth visits compare to in-person visits in the postpandemic era. Purpose: To evaluate utilization trends and patient satisfaction with virtual PT compared with in-person PT during and after the COVID-19 pandemic. Study Design: Cross-sectional study; Level of evidence, 3. Methods: We identified 59, 461 in-person and 2016 telehealth visits at a single physical rehabilitation center between March 2020 and December 2021. Patient socioeconomic and demographic variables, including insurance status, were compared between telehealth users and in-person visitors. A total of 1012 patient satisfaction surveys were available and analyzed using the top-box method. Univariable statistics ( t test or Mann-Whitney U and chi-square tests) were used for group comparisons. Results: Overall, telehealth users when compared with in-person visitors were older (median age, 47 vs 42 years, respectively; P < .001), and a higher proportion was female (60.6% vs 54.8%; P < .001), was White (69.7% vs 66.6%; P = .023), spoke English as their primary language (99.2% vs 98.1%; P = .001), and had Medicare insurance (20.3% vs 16.1%; P < .001). Telehealth patients more often lived out-of-county (50.7% vs 45.8%; P < .001) and in small towns rather than in urban areas (1.0% vs 0.3%; P < .001). When we compared telehealth use before and after official reopening of the PT center in September 2020, telehealth users in the postpandemic era had an out-of-county rate of 58.7%, and 68.7% were female. Patient satisfaction survey results demonstrated that telehealth patients compared with in-person patients were less likely to recommend visits to others (75.0% vs 89.1%, respectively; P = .008) and had lower overall assessment of their visits (71.7% vs 88.6%; P = .001). Accordingly, there was a significant reduction in telehealth visits from 2020 to 2021 (from 6.9% to 0.9% of visits; P < .001). Conclusion: We noted a decline in telehealth PT use during the postpandemic era, consistent with reduced patient satisfaction when compared with in-person visits. Telehealth is a useful option for populations with limited time or access to care and may serve a role in a hybrid care model. Further studies on long-term outcomes after telehealth PT are warranted to evaluate its efficacy.